Towards integral preservation of the values that heritage assets entails in the cuban legal framework - González Ruiz, Rosa (2023)
This article identifies the conceptual elements, instruments and relevant processes to project in the legal framework the mechanisms for the preservation of the tangible and intangible values of the assets belonging to the cultural heritage of the Cuban nation. For this purpose, it was necessary, at first, to review the specialized bibliography in order to determine the main theoretical and methodological currents that have an impact on the professional performance of architects, engineers, conservators and related personnel. Secondly, an exegesis of the legal regimes of Germany, Argentina, Belgium, Bolivia, Colombia, Ecuador, Spain, France, Italy, Portugal and Venezuela has been carried out to determine the regulatory trends in this regard. The theoretical and normative references obtained have been approached from the distinction between conservation and restoration, and the contemporary meaning of sustainability that accompanies both categories. These conceptions are relevant to examine the current legal regime for the protection of Cuban cultural heritage in order to suggest its improvement in its most integral dimension.